2016
DOI: 10.1371/journal.pone.0161939
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nlrp3 Does Not Protect Mice from Western Diet-Induced Adipose Tissue Inflammation and Glucose Intolerance

Abstract: We tested the hypothesis that loss of Nlrp3 would protect mice from Western diet-induced adipose tissue (AT) inflammation and associated glucose intolerance and cardiovascular complications. Five-week old C57BL6J wild-type (WT) and Nlrp3 knockout (Nlrp3-/-) mice were randomized to either a control diet (10% kcal from fat) or Western diet (45% kcal from fat and 1% cholesterol) for 24 weeks (n = 8/group). Contrary to our hypothesis that obesity-mediated white AT inflammation is Nlrp3-dependent, we found that Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Activation of inflammasome components has been shown in patients with chronic hepatic injury, particularly NASH, and in experimental models of NAFLD 21 , 23 . However, lack of NLRP3 was associated with reduced steatosis in some studies but it had no effects in others 21 , 46 48 . In the choline-deficient L-amino acid-defined (CDAA) model of liver injury, although not associated with features of the metabolic syndrome, inflammasome activation occurred during steatohepatitis development, whereas Nlrp3 −/− mice were protected during CDAA treatment 22 , 23 .…”
Section: Discussionmentioning
confidence: 96%
“…Activation of inflammasome components has been shown in patients with chronic hepatic injury, particularly NASH, and in experimental models of NAFLD 21 , 23 . However, lack of NLRP3 was associated with reduced steatosis in some studies but it had no effects in others 21 , 46 48 . In the choline-deficient L-amino acid-defined (CDAA) model of liver injury, although not associated with features of the metabolic syndrome, inflammasome activation occurred during steatohepatitis development, whereas Nlrp3 −/− mice were protected during CDAA treatment 22 , 23 .…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that only gene expression was measured in the present study, and the up-regulated inflammatory genes were not validated with protein measures. Although we have previously shown strong correlations between WAT inflammatory gene and protein expression 45 , future studies should measure inflammatory proteins to validate the inflammatory changes observed here.…”
Section: Discussionmentioning
confidence: 55%
“…Expression of NRLP3 components have been found to be increased in adipose tissue of obese humans and mice [24, 25] and weight loss in humans resulted in reduced expression in white adipose tissue [25]. Several animal models have demonstrated that absence of inflammasome components is associated with protection from obesity-related insulin resistance [25–27]; though there is inconsistency in this response as another group has shown that obesity-related inflammation was not associated with increased caspase-1 cleavage and Nlrp3 null mice were not protected from adipose tissue inflammation [28]. Lending further credence to a likely role of NRLP3 in obesity and metabolic dysregulation, genome wide association studies (thus far reported in Chinese Han populations) have shown association of an NLRP3 single nucleotide polymorphism with obesity [29] and with type 2 diabetes and insulin resistance [30, 31].…”
mentioning
confidence: 99%